Acute Exercise Improves Motor Memory Consolidation in Preadolescent Children - Lundbye-Jensen, Jesper; Skriver, Kasper; Nielsen, Jens B.; Roig, Marc (Frontiers in Human Neuroscience, 2017)
Objective: The ability to acquire new motor skills is essential both during childhood and later in life. Recent studies have demonstrated that an acute bout of exercise can improve motor memory consolidation in adults. The objective of the present study was to investigate whether acute exercise protocols following motor skill practice in a school setting can also improve long-term retention of motor memory in preadolescent children. Methods: Seventy-seven pre-adolescent children (age 10.5 ± 0.75 (SD)) participated in the study. Prior to the main experiment age, BMI, fitness status and general physical activity level was assessed in all children and they were then randomly allocated to three groups. All children practiced a visuomotor tracking task followed by 20 min of rest (CON), high intensity intermittent floorball (FLB) or running (RUN) with comparable exercise intensity and duration for exercise groups. Delayed retention of motor memory was assessed 1 h, 24 h and 7 days after motor skill acquisition. Results: During skill acquisition, motor performance improved significantly to the immediate retention test with no differences between groups. One hour following skill acquisition, motor performance decreased significantly for RUN. Twenty-four hours following skill acquisition there was a tendency towards improved performance for FLB but no significant effects. Seven days after motor practice however, both FLB and RUN performed better when compared to their immediate retention test indicating significant offline gains. This effect was not observed for CON. In contrast, 7 days after motor practice, retention of motor memory was significantly better for FLB and RUN compared to CON. No differences were observed when comparing FLB and RUN. Conclusions: Acute intense intermittent exercise performed immediately after motor skill acquisition facilitates long-term motor memory in pre-adolescent children, presumably by promoting memory consolidation. The results also demonstrate that the effects can be accomplished in a school setting. The positive effect of both a team game (i.e., FLB) and running indicates that the observed memory improvements are determined to a larger extent by physiological factors rather than the types of movements performed during the exercise protocol.